KONTRIBUSI USAHA TRANSPORTASI â€œOJEK PERAHUâ€ TERHADAP PENDAPATAN RUMAH TANGGA DI KELURAHAN SINDULANG KECAMATAN TUMINTING KOTA MANADO - Ruauw, Fernanda Grasela; Andaki, Jardie A.; Tambani, Grace O. (AKULTURASI: Jurnal Ilmiah Agrobisnis Perikanan, 2018)
AbstractBoats are the choice for transportation activities on the river. The condition of the Tondano River, specifically at the river mouth is suitable for boat crossings. The need to move from one side of the river to the other side of the river with various needs, raises remuneration for "mining" boats / ojek boats. Opinions generated from this remuneration contribute to family income.The objectives of this study, namely: 1) identify the activities of "mining" boat / ojek boat transportation in the Tondano River Estuary of Manado City; and 2) determine the contribution of "mining" boat / ojek boat transportation activities in the Tondano River Estuary of Manado City to family income.The subjects of this study were the people in Sindulang I and Sindulang II Subdistrict Tuminting Sub-District, Manado City who carried out the business of "mining" boats / ojek boats. While the objects in this study were household income in Sindulang I Village and Sindulang II Tuminting District, Manado City.Analysis technique is an attempt to determine the answer to the question about the formula and the things obtained in a study. Data that has been entered and collected is analyzed to answer the research objectives. Data analysis techniques are adjusted to the research objectives. The data analysis techniques used in this study are as follows:Analysis of the contribution of boat mining / ojek boat businesses to total household income is carried out by the percentage method. Contributions are contributions that can be given by something to other things. The data obtained were analyzed without statistical tests by calculating the amount of money obtained from a business activity "boat mining" / ojek boat and total household income multiplied by one hundred percent.The results of the research and discussion can be concluded: 1) boat motorcycle taxi activities carried out in the form of ferry services and boat rental services for use as a means of fishing or fishing activities; 2) the contribution of boat motorcycle taxis to family income is 81.97%, while the remaining 18.03% is contributed by other businesses outside the boat ojek business; 3) outpouring of work time causes the contribution of boat motorcycle taxis to be greater than the contribution of other businesses outside the boat ojek business.Keywords: transportation, boat motorcycle taxi, activities, contributionsÂ AbstrakPerahu menjadi pilihan untuk aktivitas transportasi di sungai. Kondisi Sungai Tondano, khusus pada muara sungai cocok untuk penyeberangan menggunakan perahu. Kebutuhan untuk berpindah dari satu sisi sungai menuju sisi lain dari sungai dengan berbagai keperluan, menimbulkan balas jasa bagi perahu â€œtambanganâ€ / ojek perahu. Pendapat yang dihasilkan dari balas jasa ini berkontribusi terhadap pendapatan keluarga. Tujuan dari penelitian ini, yaitu : 1) mengidentifikasi aktivitas transportasi perahu â€œtambanganâ€ / ojek perahu di Muara Sungai Tondano Kota Manado; dan 2) menentukan kontribusi aktivitas transportasi perahu â€œtambanganâ€ / ojek perahu di Muara Sungai Tondano Kota Manado terhadap pendapatan keluarga.Subjek penelitian ini adalah masyarakat di Kelurahan Sindulang I dan Sindulang II Kecamatan Tuminting Kota Manado yang menjalankan kegiatan usaha perahu â€œtambanganâ€ / ojek perahu. Sedangkan objek dalam penelitian ini adalah pendapatan rumah tangga di Kelurahan Sindulang I dan Sindulang II Kecamatan Tuminting Kota Manado.Teknik analisis merupakan suatu usaha untuk menentukan jawaban atas pertanyaan tentang rumusan dan hal-hal yang diperoleh dalam suatu penelitian. Data yang sudah masuk dan terkumpul dianalisis ubtuk menjawab tujuan penelitian. Teknik analisis data disesuaikan dengan tujuan penelitian. Adapun teknik analisis data yang digunakan dalam penelitian ini adalah sebagai berikut:Analisis kontribusi usaha perahu â€œtambanganâ€ / ojek perahu terhadap pendapatan total rumah tangga dilakukan dengan metode persentase. Kontribusi adalah sumbangan yang dapat diberikan oleh suatu hal terhadap hal lain. Data yang diperoleh dianalisis tanpa uji statistik dengan menghitung jumlah uang yang diperoleh dari suatu kegiatan usaha perahu â€œtambanganâ€ / ojek perahu dan pendapatan total rumah tangga dikali seratus persen.Hasil penelitian dan pembahasan dapat ditarik kesimpulan: 1) aktivitas ojek perahu dilakukan dalam bentuk jasa penyeberangan dan jasa sewa perahu untuk penggunaan sebagai sarana aktivitas pemancingan atau mencari ikan; 2) kontribusi usaha ojek perahu terhadap pendapatan keluarga sebesar 81,97%, sedangkan sisanya 18,03% dikontribusi dari usaha lain di luar usaha ojek perahu; 3) curahan waktu kerja menyebabkan kontribusi pendapatan ojek perahu lebih besar dari kontribusi usaha lain di luar usaha ojek perahu.Kata kunci : transportas, ojek perahu, aktivitas, kontribusi